2011
DOI: 10.1007/s10549-011-1857-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic differentiation of malignant from benign breast lesions: a meta-analytic comparison of elasticity and BIRADS scoring

Abstract: There has been controversy regarding the accuracy of breast ultrasound elastography (USE) compared to conventional B-mode Ultrasound (USB). The purpose of this study was to conduct a direct comparative effectiveness analysis of USB versus USE or their combination in differentiating breast lesions through systematically reviewing recent literature. An extensive literature search of PubMed and other medical and general purpose databases from inception through August 2011 was conducted. Published studies that rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 49 publications
9
52
0
7
Order By: Relevance
“…By combining BI-RADS classification with TS and SR, specificity, PPV and NPV increased. This is in line with other published data [2,23,24] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…By combining BI-RADS classification with TS and SR, specificity, PPV and NPV increased. This is in line with other published data [2,23,24] .…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in line with the sensitivity and specificity of 96% (56-100%) and 70% (21-99%), respectively, reported by Sadigh et al [2] in their meta-analysis. For TS, our study reveals a sensitivity of 39%, which is lower than the average 79% reported by Sadigh et al [2] , although 39% is still within the range they observed (35-97%). Our values for TS specificity were more similar to theirs, with 94% in our study compared to 88% (70-99%) in theirs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Its diagnostic power has been reported in several publications (Farrokh et al 2011;Wojcinski et al 2010). A recent meta-analysis of 5511 lesions indicated that elastography has a sensitivity of 79% and a specificity of 88% when the Tsukuba elasticity score is used (Sadigh et al 2012). Several studies have reported that B-mode ultrasound has a higher sensitivity and a lower specificity than elastography.…”
Section: Introductionmentioning
confidence: 92%
“…Quantifiable results can also be reproducibly represented. In 2012 Sadigh et al conducted a first large metaanalysis regarding the use of ultrasound elastography (USE) for the differentiation of focal breast lesions compared to B-mode imaging (USB) and the combination of the two methods (dependent and independent) [44,45]. It was shown on the basis of 5,511 breast lesions that elastography alone increases the specificity from 70 % (USB) to 88 % (USE) but came at the price of a partially reduced sensitivity (96 % vs. 79 %), while the number of correct classifications did not differ significantly.…”
Section: Shear Wave Elastographymentioning
confidence: 99%